The Impact of Digital Content Marketing on Brand Equity and Purchase Intention: A Study of Green Food Packaging in Thailand - Vitayapiruks, Rueshapon; Nutittamont, Wasutida; Phayaphrom, Bordin (International Review of Management and Marketing, 2026)
The shifting consumer preference towards eco-friendly packaging and rising awareness regarding the negative effects of traditional packaging on the environment is augmenting the demand for the green packaging. This research aims to reveal the effect of green packaging of food products, which is communicated through digital content marketing activities on social media, which further affects the brand and purchase intention. The research emphasizes the concepts of digital content marketing, customer-based brand equity, and purchase intention. This study assessed the effect of Digital Content Marketing (DCM) of food products with green packaging on customer-based brand equity’s dimensions, including Brand Awareness (BA), Brand Image (BI), and Brand Loyalty (BL); and then the effect of DCM on the Purchase Intention (PI) among Gen Y consumers in Thailand. The study also assessed the interrelation among the customer-based brand equity’s dimensions (BA, BI, and BL) and their effects on the Purchase Intention (PI).